Fenomena Sufiks Pada Adjektiva dalam Surah Al-Nisa>’ dan Makna Morfologinya - Syafri, Ratna; Nur Salimova, Fernanda Venturini (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2023)
A suffix is an affix added to the end of a basic form. In Arabic, the suffix is known as al-lawãhiq. The suffix or al-lawãhiq is one of the most minor elements of a language unit with meaning. Thus, the suffix or al-lawãhiq can be referred to as a morphem. The suffix or al-lawãhiq has various meanings according to its form. Therefore, this study aims to uncover the forms of suffixes on adjectives contained in surah al-Nisã’ and uncover their meanings. To reveal this, this research uses theories related to morphemes as a foundation for solving research problems. The research method used in this study is descriptive analysis with a qualitative approach. The results of this study show that the suffix form of the adjective contained in surah al-Nisã’ there are five forms, namely al-Wãw and al-Nûn or al-Yã’ and al-Nûn, al-Alif and al-Nûn or al-Yã’ and al-Nûn, al-Tanwîn, Ta al-Marbuthah + Tanwîn, and the last one al-Alif and al-Tã’ + Tanwîn. The morphological meaning of the suffixes is single, dual, and plural numbers (JAMA); types are masculine and feminine; Clarity is indefinite.